Cultural Conditions of Constructing Hegemonic Masculinity in the Polish Environment of West Prussia in the in the Mid-19th Century - Śpica , Paweł (Biuletyn Historii Wychowania, 2023)
The article presents cultural factors contributing to hegemonic masculinity in the Polish community of West Prussia in the mid-19th century. Starting from the perspective of social constructionism, Raewyn Connell’s theory of hegemonic masculinity was used in the research process to reveal the dominant discourse of masculinity in the studied milieu. The source base for the research was the Polish journalism of the region in question (predominantly the local press), mainly from the late 1840s and 1850s, less frequently from later periods. The contextual analysis of the research material made it possible to identify five basic, cultural determinants cultivating hegemonic masculinity in the Polish community of West Prussia in the period studied, analysed in detail (in separate parts) in the present article. These determinants include: the dominant narrative on the role of the male in the family, the position of the male in social structure, the role of the insurrectionary and organic work ethos, the influence of professed faith, including the views proclaimed by Catholic moralists, and the resulting beliefs about male sexuality. The research has shown the significant influence of Catholic ethics and national ideas derived from the nobility on the creation of a hegemonic image of masculinity in the Polish community of the studied region. This discourse was explicitly conservative and essentialist in nature. It also played an important role in maintaining and developing Polish identity in the absence of the Polish statehood.